Microencapsulation techniques to develop formulations of insulin for oral delivery: a review. (13th December 2012) - Cárdenas-Bailón, Fernando; Osorio-Revilla, Guillermo; Gallardo-Velázquez, Tzayhrí
Abstract : Oral insulin delivery represents one of the most challenging goals for pharmaceutical industry. In general, it is accepted that oral administration of insulin would be more accepted by patients and insulin would be delivered in a more physiological way than the parenteral route. From all strategies to deliverer insulin orally, microencapsulation or nanoencapsulation of insulin are the most promising approaches because these techniques protect insulin from enzymatic degradation in stomach, show a good release profile at intestine pH values, maintain biological activity during formulation and enhance intestinal permeation at certain extent. From different microencapsulation techniques, it seems that complex coacervation, multiple emulsion and internal gelation are the most appropriate techniques to encapsulate insulin due to their relative ease of preparation. Besides that, the use of organic solvents is not required and can be scaled up at low cost; however, relative oral bioavailability still needs to be improved.